School Operational Assistance and the Future of Financial Management in the Education Sector - Rudolf Lumbantobing (AL-ISHLAH: Jurnal Pendidikan, 2021)
This study aims to analyze the School Operational Assistance and the Future of Financial Management in the Education Sector. The approach used in this research is a qualitative method with a descriptive course. The types of data used in this research are primary and secondary data. Preliminary data were obtained from in-depth interviews and questionnaires with informants through purposive sampling technique; the respondents in this research were 65 people, including school administrators and school committees. At the same time, secondary data is obtained from the literature study to acquire and build an abstraction about the research objectives and data support so that general conclusions can be made to specific. This research is conducted on Junior High Schools in West Jakarta, which received School Operational Assistance funds. Based on the results of data analysis, it can be concluded that Junior High Schools in West Jakarta in terms of planning, implementation, and accountability indicators are in the very effective category. This is due to the school's financial management that applies three main strategies, namely Strategic Planning, Strategic Management, and Strategic Thinking.